PENGARUH TEKANAN PERAN DAN GAYA KEPEMIMPINAN TERHADAP KINERJA JASA PENILAI: Pipin Fitriasari, STIE Madani Balikpapan - fitriasari, pipin (STIE Madani Balikpapan, 2023)
The purpose of this research is to determine and obtain empirical evidence on the factors related to the behavior of appraisers that could affect the performances of appraisers who work in Public Appraisers Firm (KJPP). This research discusses the factors regarding role conflict, role ambiguity, role excess, and leadership style. Researcher obtained data through questionnaires distributed directly to the appraisers who attended the workshop. The researcher deployed 30 questionnaires which all the samples were used in study. To obtain the result of the study, researcher used PLS Smart Analysis 3.0. The result of this study indicate that role overload and leadership style, have a significant influence on the performance of appraisers. While, role conflict, and role ambiguity do not significantly affect the performance of appraisers.